Insecticide application effect on ground dwelling arthropods in edamame crops - Hasibuan, Rosma; Cindowarni, Olivia; Kamal, Muhammad; Purnomo, Purnomo; Karyanto, Agus (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2025)
Ground-dwelling arthropods play many important roles in agroecosystems. This experiment was conducted to assess the effects of botanical and synthetic insecticides on soil arthropods in edamame crops. The study included six treatments: soursop leaf extract at concentrations of 1% and 2%, diflubenzuron at concentrations of 0.05% and 0.1%, a common synthetic insecticide (chlorantraniliprole 0.15%), and a control (untreated plants), each with three replications. Pitfall traps were used to sample soil arthropods. A total of 2222 soil arthropods were collected, consisting of 1443 (64.94%) predatory arthropods and 778 (35.06%) detritivorous arthropods. The dominant orders of predators and detritivores were Araneae (61.5%) and Coleoptera (40.2%), respectively. The highest numbers of predatory and detritivorous arthropods were found on edamame plants sprayed with soursop extract, while the lowest numbers were recorded on plants treated with the common synthetic insecticide chlorantraniliprole. These results indicate that chlorantraniliprole negatively impacts the presence of ground-dwelling arthropods in edamame agroecosystems. In contrast, the application of the botanical insecticide (soursop leaf extract) and the synthetic insect growth regulator (diflubenzuron) did not reduce the abundance or diversity of ground-dwelling arthropods in edamame fields.